Factors influencing knowledge, attitude and practices of adult Filipinos on pharmaceutical waste disposal in Manila, Philippines - Quijano, James Paul A.
Improper waste segregation remains a problem in the Philippines. Pharmaceutical waste, a type of waste derived from disposed unused, unwanted, and expired medications, could lead to unfavorable impacts to humans, animals, and the environment. Households can serve as a primary source of pharmaceutical waste. Hence, the study aims to determine the factors influencing the knowledge, attitudes, and practices on pharmaceutical waste disposal in Manila, Philippines.